(3QhVI GdCYdGe HefRdI GdYQHjI ef Ydhe GdESdGes - (3CHh YHO Gddg TeS GdOjf eMeO Hf Ydj Hf eMeO GdGUHMj GdCfOdSj, GHf GdGRQb,J (B896 (3g` s
(3ChdgG (B:s
(3GdeSdc GdChd hJbQjQg ef hLhg , CMOgG Cf GdMV Ydi MH GdYQH HfMh eG ai GdUMjM , Yf GHf YeQ (B( (3QVi Gddg Yfg (B) (3Cf QShd Gddg (B( (3Udi Gddg Ydjg hSde (B) : (3ef CMH GdYQH s
(3BNQgG (B:s
(3hdh jchf Gdbhd ai GdbjGS , EPG dcGf GdUeJ ef MHd GdPgH hbO Je HYhf Gddg Jcejd gPG GdZQV eG JYGbH Gddjd hGdfgGQ , hYeQ HJQ OjOgG GdSQ hGdLgGQ s
(3Cdag ai eOjfI eGdbIs
(3SfI (B875(3g`s
(3efRdI Yf fSNI cJHJ ai eOjfI eGdbI SfI (B886 (3g` ai MjGI GdeDdas
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GddZIs